Evaluation of the Accuracy of ADAS Module Readings Based on an Analysis of the Transient Supply Current and Neural Network Application - Grzechca, Damian; Rybka, Pawel; Paszek, Krzysztof (Elektronika ir Elektrotechnika, 2018)
The following paper presents advanced methods for evaluating the reliability of ADAS module readings, based on an analysis of the transient supply current. Changes in the transient current waveform occur due to environmental conditions and damage to a module’s inner circuitry. Specific deviations in the waveforms may indicate a certain event – either internal or external. This paper presents how to successfully distinguish certain anomalies using artificial neural network-based classification algorithms without having to interfere with the module’s internal circuitry. DOI: http://dx.doi.org/10.5755/j01.eie.24.3.20944